BIPOLAR DISORDER IN JOHN GREEN’S THE FAULT IN OUR STARS - Hans Mitra Wijaya (LINGUA LITERA : journal of english linguistics and literature, 2018)
This research analyzes Bipolar Disorder that is portrayed in a novel entitled the Fault in Our Stars. The problem found in this research is the symptoms of BipolarDisorder and the main character ways in overcoming it. The purpose of research is to find out which Bipolar Disorder symptoms occur in the novel. In resolving the issue, the researcher uses the theory of Bipolar Disorder by Norman Sartorius. The concepts used are Manic episode and Depressive episode. Each of the Manic and Depressive episode has their own symptoms. The research method used by the researcher is a qualitative research method. The researcher finds several symptoms that Hazel has and Hazel ways in overcoming the Bipolar Disorder that is family support and keep fighting. She overcomes the Bipolar Disorder by getting supportfrom her family which make she could withstand her disease.